Effect of mixed spices on hyperglycemia in case controlled type 2 Diabetes Mellitus (T2DM): a preliminary report - Mahmood, Tahir; Khattak, Muhammad Muzaffar Ali Khan; Mohd Shukri, Nur Hannan; Azam , Siti Amirah; Shamsudin, Nurul Aimi (2014)
Twenty type 2 diabetes mellitus (T2DM) patients were recruited from the Medical Out-patient Department of Hospital Tengku Ampuan Afzan Kuantan, Malaysia. Ten patients were provided with the Placebo and another ten were served with 4 gram of mixed spices daily for 30 days. Blood samples were collected before and at the end of the feeding period and analyzed for the parameters namely Fasting Blood Sugar (FBS), Glycosylated Hb (HbA1c) and Lipid Profile. The collected data was analyzed using SPSS Statistical Software version 12. During the consumption period the patients tolerated mixed spices well with an improvement in their general well being. The result revealed that FBS and total cholesterol were significantly (p<0.05, P<0.001) reduced. This preliminary clinical trial shows that the formulated spices have positive effect in T2DM patients.